PREFERENCE DEVELOPMENT OVER ETAILING AMONG GENERATION COHORTS: A CONCEPTUAL FRAME WORK AND RESEARCH PROPOSITIONS - S.Jenifer, Dr. Arockia Mary. R (International Journal of Advanced Science and Technology, 2020)
The study comprises of different aspects as consumer behavior in digital world, impact of e-tailing on consumer buying decision making process, nature of e tailing among generation cohorts, variation in buying decision making process among the generation cohorts and finally the impact of e-tailing on buying decision process among the generation cohorts are compiled for logical understanding.